2012
DOI: 10.1074/jbc.m112.345710
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory IgG Production Requires Functional P1 Promoter in β-Galactoside α2,6-Sialyltransferase 1 (ST6Gal-1) Gene

Abstract: Background: ␤-Galactoside ␣2,6-sialyltransferase 1 (ST6Gal-1) action is essential for the anti-inflammatory activity in intravenous immunoglobulin (IVIG) therapy. Results: Fc sialylation changes in accordance to the severity of inflammation. Inactivation of the P1 promoter abrogated IgG Fc sialylation. Conclusion: Fc sialylation depends on ST6Gal-1 in the circulation. Defective Fc sialylation is a mechanism for the generally proinflammatory tendencies of the P1-ablated mutant mouse (Siat1⌬P1). Significance: An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 28 publications
5
42
0
1
Order By: Relevance
“…2 A and B). However, compared with the untreated state, a decrease in the amount of sIgG was seen after sensitization, consistent with previous studies (2,14). Importantly, the percentage of OVA-specific IgG in both strains was also found to be equivalent (wild type = 6.8 ± 1.12%; cKO = 6.5 ± 1.06%), demonstrating the lack of B-cell defects associated with the loss of ST6Gal1.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…2 A and B). However, compared with the untreated state, a decrease in the amount of sIgG was seen after sensitization, consistent with previous studies (2,14). Importantly, the percentage of OVA-specific IgG in both strains was also found to be equivalent (wild type = 6.8 ± 1.12%; cKO = 6.5 ± 1.06%), demonstrating the lack of B-cell defects associated with the loss of ST6Gal1.…”
Section: Resultssupporting
confidence: 90%
“…Germ-line ablation of ST6Gal1 eliminates α2,6-linked sialic acids on IgG and essentially all other glycoproteins in the body (10,11) with the exception of those in the central nervous system (12). Moreover, modification of the P1 region of the ST6Gal1 promoter generated defects in both myelopoiesis (13) and sialylation of serum glycoproteins (14). Here, we describe the creation of a B-cell-specific knockout of ST6Gal1 that was created to more fully understand the impact of IgG sialylation on autoimmunity.…”
mentioning
confidence: 99%
“…Using a mouse model, it has been reported that ST6Gal-1 deletion results in more severe pulmonary inflammation [99], consistent with the importance of sialic acid in anti-inflammation [54,56]. Recently, ST6Gal-1 driven by liver-specific promoter P1 in the systemic circulation was shown to be important for the addition of α2,6-sialic acid on the serum IgG Fc glycan [100]. As the P1 promoter does not induce the expression of ST6Gal-1 in B cells, the reduction in serum sialylated IgG in P1-deficient mice is attributed to the decreases in circulatory ST6Gal-1 [100].…”
Section: Igg Glycovariants Under Physiological and Patho-physiologicamentioning
confidence: 58%
“…Recently, ST6Gal-1 driven by liver-specific promoter P1 in the systemic circulation was shown to be important for the addition of α2,6-sialic acid on the serum IgG Fc glycan [100]. As the P1 promoter does not induce the expression of ST6Gal-1 in B cells, the reduction in serum sialylated IgG in P1-deficient mice is attributed to the decreases in circulatory ST6Gal-1 [100].…”
Section: Igg Glycovariants Under Physiological and Patho-physiologicamentioning
confidence: 99%
“…There is growing evidence that the IgG1 Fc N-glycan composition changes in response to disease. [44][45][46][47][48] Our data indicate variations in Fc N-glycan composition profiles alter relative FcgR binding affinities. Considering the tissue-specific expression profile for the FcgRs, 3 changes to the IgG1 Fc N-glycan composition therefore have the potential to direct which leukocyte populations are affected and, as a result, direct the body's response to infection.…”
Section: Discussionmentioning
confidence: 69%